Development of Digital Learning Media Helped Capcut on Theme Care Against Living Things in Class IV SD - Ira Amalia Harahap; Dinda Yarshal (PT Inovasi Pratama Internasional, 2023)
This research is to find out the Development of CapCut-Assisted Digital Learning Media on the Theme of Caring for Living Creatures. The research design that I used in this study was Development or Research and Development (R&D). The model used in this development is the ADDIE model. The research subjects of the development of CapCut-assisted digital learning media are media design experts, material experts. The object in this study is CapCut-assisted digital learning media on the theme of caring for living things which was created to assist teachers in thematic learning of class IV SD. Research on product development in the form of digital learning media assisted by CapCut on the theme of caring for living things for class IV SD NEGERI 0209 BAHAL BATU, which will be carried out in June 2023. To analyze the data collected from the questionnaire it can be grouped into 2 types of data, namely descriptive qualitative and quantitative descriptive. Qualitative data were obtained from a questionnaire containing criticism and suggestions from media and material validator experts. The data obtained as a reference for revising the product being developed. The data obtained as a guideline for revising the resulting product. Based on the results of the calculations above, the overall assessment results from material experts reach 70%. If the percentage obtained reaches 61% to 80% then the CapCut-assisted digital learning video is categorized as feasible. From the calculation above, it is obtained that the percentage is 70%, so the CapCut video is categorized as feasible. Based on the results of material expert validation, learning material on the theme of caring for living things through CapCut interactive video is feasible to be developed in science learning with a percentage of 80%, this means that learning media is included in the